A Mobility Model for Connected Vehicles Induced by the Fish School - Daxin Tian; Keyi Zhu; Jianshan Zhou; Jian Wang; Guohui Zhang; He Liu (International Journal of Distributed Sensor Networks)
We proposed a mobility model of connected vehicles with wireless communications. The proposed mobility model is inspired by the fish school, which takes into account several significant attractive/repulsive potential fields induced by the expected mobility, the tendency to avoid collisions, and the road constraints. With this model, we present a comprehensive approach for designing and analyzing the potential fields acting on connected vehicles. Based on the Lyapunov stability theorem, a theoretical analysis is also provided to show that the cooperative collision avoidance and stable constrained flocking of connected vehicles can be performed by using this model. The numerical experiments prove the effectiveness of the wireless communication on the safety and efficiency of connected vehicles.